2003
DOI: 10.1186/1297-9686-35-s1-s113
|View full text |Cite
|
Sign up to set email alerts
|

Association studies using random and "candidate" microsatellite loci in two infectious goat diseases

Abstract: We established a set of 30 microsatellites of Bovidae origin for use in a biodiversity study in Swiss and Creole goats. Additional microsatellites located within or next to "candidate" genes of interest, such as cytokine genes (IL4, INF-gamma) and MHC class II genes (DRB, DYA) were tested in the caprine species in order to detect possible associations with two infectious caprine diseases. Microsatellite analysis was undertaken using automated sequencers (ABI373 & 3100). In the first study, a total of 82 unrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…associated with genes of known function), transcript-associated microsatellites also represent ideal markers for studying the genetic basis of phenotypic trait variation [13]. However, despite several studies having developed panels of candidate-gene targeted microsatellites from the complete genome sequences of humans and their companion species [41][43], cDNA has not yet been widely exploited for this purpose, particularly in non-model organisms. Our study highlights the eminent feasibility of such an approach, although the numbers of markers obtainable will clearly depend on the relative abundance of various classes of transcript.…”
Section: Discussionmentioning
confidence: 99%
“…associated with genes of known function), transcript-associated microsatellites also represent ideal markers for studying the genetic basis of phenotypic trait variation [13]. However, despite several studies having developed panels of candidate-gene targeted microsatellites from the complete genome sequences of humans and their companion species [41][43], cDNA has not yet been widely exploited for this purpose, particularly in non-model organisms. Our study highlights the eminent feasibility of such an approach, although the numbers of markers obtainable will clearly depend on the relative abundance of various classes of transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at linked microsatellites there are allelic correlations to disease resistance in both sheep (Coltman et al . 2001) and goats (Obexer‐Ruff et al . 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, novel microsatellites often have to be isolated before they can be utilized for each species, which generally demands considerable time and high cost. Recently many studies have demonstrated cross-species amplification of Bovidae microsatellites in the Caprinae, allowing possible population studies on species for which microsatellites are not yet developed (Li et al 2002;Obexer et al 2003;Saitbekova et al 1999). This approach is advantageous to the study of endangered species, which might have reduced genetic variation (Maudet et al 2001).…”
mentioning
confidence: 99%